Sustained consumption of cocoa-based dark chocolate enhances seizure-like events in the mouse hippocampus. Issue 3 (12th February 2018) - Cicvaric, Ana; Bulat, Tanja; Bormann, Daniel; Yang, Jiaye; Auer, Bastian; Milenkovic, Ivan; Cabatic, Maureen; Milicevic, Radoslav; Monje, Francisco J.
Abstract : This study characterizes the effects of sustained dark-chocolate consumption on mouse behavior and reveals its potential to induce seizure-like events in the hippocampus, a brain structure critical for memory storage. Abstract : While the consumption of caffeine and cocoa has been associated with a variety of health benefits to humans, some authors have proposed that excessive caffeine intake may increase the frequency of epileptic seizures in humans and reduce the efficiency of antiepileptic drugs. Little is known, however, about the proconvulsant potential of the sustained, excessive intake of cocoa on hippocampal neural circuits. Using the mouse as an experimental model, we examined the effects of the chronic consumption of food enriched in cocoa-based dark chocolate on motor and mood-related behaviours as well as on the excitability properties of hippocampal neurons. Cocoa food enrichment did not affect body weights or mood-related behaviours but rather promoted general locomotion and improved motor coordination. However, ex vivo electrophysiological analysis revealed a significant enhancement in seizure-like population spike bursting at the neurogenic dentate gyrus, which was paralleled by a significant reduction in the levels of GABA-α1 receptors thus suggesting that an excessive dietary intake of cocoa-enriched food might alter some of the synaptic elements involved in epileptogenesis. These data invite further multidisciplinary research aiming to elucidate the potential deleterious effects of chocolate abuse on behaviour and brain hyperexcitability.